2023
DOI: 10.1002/cpp.2807
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapted psychological intervention for treating maternal depression in British mothers of African and Caribbean origin: A randomized controlled feasibility trial

Abstract: Background: Women are likely to suffer from maternal depression due to childbirth difficulties and parenting responsibilities, leading to long-term negative consequences on their children and families. British mothers of African/Caribbean origin uptake of mental healthcare is low due to the lack of access to culturally appropriate care. Methods: A mixed-methods randomized controlled feasibility trial was adopted to test the appropriateness and acceptability of Learning Through Play plus Culturally adapted Cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The value implication of cultural appropriateness in maternal mental health care is consistent in African/Caribbean mothers ( 24 ). For example, in another study in Kenya, LTP+CaCBT was found to be culturally appropriate and acceptable for treating postnatal depression in rural, low-income and socio-economically disadvantaged women ( 32 ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The value implication of cultural appropriateness in maternal mental health care is consistent in African/Caribbean mothers ( 24 ). For example, in another study in Kenya, LTP+CaCBT was found to be culturally appropriate and acceptable for treating postnatal depression in rural, low-income and socio-economically disadvantaged women ( 32 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, it is worth mentioning the cautionary observations made in Jidong et al. ( 24 ) and Notiar et al. ( 32 ) studies which were both feasibility trials with primary outcome measures testing the appropriateness and acceptability of the LTP+CaCBT intervention with small sample sizes of the former n=26 (double arm) and the later n=19 (single arm).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations